JavaScript Cookbook - Powers, Shelley (O'Reilly Media, 2012)
Why reinvent the wheel every time you run into a problem with JavaScript? This cookbook is chock-full of code recipes that address common programming tasks, as well as techniques for building web apps that work in any browser.